Enzymatic degradation of mycotoxin patulin by an extracellular lipase from Ralstonia and its application in apple juice. (June 2022) - He, Qian; Liang, Jingyimei; Zhao, Yuning; Yuan, Yahong; Wang, Zhouli; Gao, Zhenpeng; Wei, Jianping; Yue, Tianli
Abstract: Patulin is a widespread mycotoxin which constitutes serious threats to human health. Biological strategies that utilize microbial enzymes have shown to be promising in the control of patulin contamination. In this study, a lipase (RL12) from the isolated strain Ralstonia sp. SL312 was successfully purified and studied for the degradation of patulin. Degradation assays for patulin by RL12 were systematically performed both in aqueous solution and apple juice. The results of this analysis revealed that the optimal pH and temperature were 7.5 and 37 °C, respectively. The addition of RL12 at 100 μg/mL permitted degradation of over 80% of patulin in apple juice within 24 h, and the enzymolysis procedure may enhance the nutritional and sensory qualities of apple juice. Possible degradation product of patulin was also proposed. The use of lipase RL12 could be an important bio-control measure to detoxify patulin. Highlights: Culture supernatant of isolated strain exhibited patulin removal effect. An extracellular lipase was successfully purified. Purified lipase RL12 was successfully used for patulin degradation. Possible degradation product of patulin was proposed. Nutritional and sensory quality of apple juice increased after degradation.